URGENSI SILATURAHMI DALAM PERSPEKTIF HADIS - Diyanna, Diyanna; Qurotul Aini, Nadiyya; Alif, Muhammad (Program Studi Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2023)
Gathering has become a culture that is closely related to the social life of society in Indonesia and is very crucial from an Islamic perspective, especially for a green future with sustainable Islamic values. Even the Prophet Muhammad SAW strongly recommended keeping in touch with each other, as has been mentioned in many hadiths. This research aims to discuss the urgency of Gathering from a hadith perspective to create a green future of Islamic values. The formulation of the problem in this research is how the hadith views the urgency of Gathering as an important factor for creating a green future of Islamic values. In this research, a qualitative approach was used with the application of the hadith thematic method. The formal object of this research is the understanding and urgency of Gathering which is formulated of the hadith theme. Then the results obtained indicate that the theme of hadith can be formulated into a theoretical framework about the urgency of Gathering in the perspective of hadith and gathering is very much needed in efforts to realize a green future of Islamic values. The discussion in this study explains that the urgency of Gathering is highly recommended by the prophet and has a special place because it has a direct relationship with Allah so that it will have a bad impact if it breaks the Gathering. The conclusion of this study is that Gathering has a crucial urgency for society and life so that it has a reciprocal impact and has various types according to the purpose of carrying out Gathering and can help in realizing a green future of Islamic values.